Peningkatan Kemampuan Memecahkan Masalah melalui Kegiatan Eksperimen Sains pada Anak Kelompok B di Taman Kanak-kanak Fitri 2 Kota Bengkulu - Helena Sunarni; Yaswinda Yaswinda (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
Problem-solving skills are essential competencies that should be developed from an early age because they help children think logically, understand cause-and-effect relationships, make decisions, and solve simple problems encountered in daily life. However, preliminary observations at Fitri 2 Kindergarten, Bengkulu City, indicated that the problem-solving abilities of Group B children had not developed optimally. This study aimed to improve children's problem-solving skills through a science evaporation experiment activity. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, acting, observing, and reflecting stages. The participants were 12 children aged 5–6 years in Group B at Fitri 2 Kindergarten, Bengkulu City. Data were collected through observation, documentation, field notes, and simple interviews. The data were analyzed using descriptive quantitative techniques by calculating the percentage of children's achievement on each problem-solving indicator across the research cycles. The findings revealed that the science evaporation experiment effectively improved children's problem-solving skills in all observed indicators, including observing changes during experiments, explaining the causes of evaporation, comparing experimental results, identifying simple problems, attempting solutions, communicating observations, and drawing conclusions. The average level of children's problem-solving skills increased from 41.67% in the preliminary condition to 66.67% in Cycle I and further improved to 91.67% in Cycle II. The improvement occurred because the science experiment provided children with direct, meaningful, and hands-on learning experiences that encouraged active exploration, logical thinking, understanding of cause-and-effect relationships, and independent problem-solving. Therefore, science evaporation experiments can be used as an effective learning strategy to enhance problem-solving skills among early childhood learners